Makna Sosial Masyarakat Bagi Penerima Bantuan Langsung Tunai di Desa Bonto Manai Kabupaten Bulukumba - Syahban Nur; Muhammad Yusuf Daeng Pangeran (Almeera Education, 2022)
The Covid-19 pandemic began to enter Indonesia in January 2020 and began to affect the Indonesian state from various sectors, it can even be said that Covid-19 was able to change the country of Indonesia as a whole, especially from the economic sector. South Sulawesi, positive cases of Covid-19 increased by 29 on May 27, 2020, with this addition, positive cases in South Sulawesi have reached 1381 cases, in this case the government in South Sulawesi began to implement PSBB, especially in the city of Makassar PSBB on December April 24, 2020, to combat the spread of the Corona virus, the impact of the implementation of the PSBB in the city of Makassar is very significant, even all regions in South Sulawesi are also affected by the implementation of the PSBB. This type of research uses a qualitative descriptive method, including a series of systematic activities to get answers to the problems posed when viewed from the type of object studied, so this researcher is categorized as a case study researcher with the aim of providing an overview of the Social Meaning of Direct Assistance Recipients (BLT) During Covid-19 pandemic. This research will be carried out in less than three months from September to October 2020 in Desah Bontomanai, Rilau Ale District, Bulukumba Regency.